Helyi értékek nyomában: közösségi tevékenységek Baranya megyében a 19. századtól napjainkig - Őri , László; Nemeskéri , Zsolt; Zádori , Iván (Kultúratudományi Szemle, 2022)
Community Activities in Baranya County from the 19th Century to the Present László Őri – Zsolt Nemeskéri – Iván Zádori The second half of the 19th century was an important turning point in the community processes and activities of Baranya County: parallel with the economic and social development, the first non-governmental organizations also appeared and became more and more important in the local society and economy. The exploration of these civic activities from the 19th century to the present day took place in 2021 and our results cer tainly enriched the earlier findings of this topic as well. Our present study attempts to summarize these research results, focusing on the most important features of the community activities and social movement processes of Baranya County. However, the study is not only a summary of our results, but also the first study that presents our findings, and it will be followed by other publications that clearly show the importance and the role of the past and the present community activities and non-profit organizations of Baranya County.